Profil Peresepan Terapi Infeksi Saluran Pernafasan Atas di Apotek Murni Periode Januari - Maret 2021 - Puji Lestari; Meiti Rosmiati (Publikasi Indonesia, 2022)
Upper Respiratory Tract Infection is one of the diseases with high morbidity and mortality rates. This disease is caused by a variety of microorganisms and can cause infection. Deaths caused by these infections occur 2-6 times higher in developing countries. The purpose of this study was to determine the profile of prescribing therapy for upper respiratory tract infections at Apotek Murni Bekasi for the period January - March 2021, based on the classification and order of the most drug use. The method used is descriptive and retrospective collection using secondary data on prescription drugs for upper respiratory infections that meet the criteria. The study was conducted in January - March 2021. The instrument used was prescription data for patients with Upper Respiratory Tract Infections. Samples were taken by simple random sampling with a significant level of 5%. The samples taken were all prescriptions for the use of upper respiratory tract infection drugs as many as 337 prescription samples. The results of the study from 337 samples of treatment therapy for Upper Respiratory Tract Infections based on the drug class that had the most prescriptions were respiratory drugs with a frequency of 110 (46. 41%) and a total use of 402 (31. 50%), analgesic-antipyretic with a frequency of 40 ( 16. 87%) and the number of uses 255 (19. 98%), antibiotics with a frequency of 27 (11. 39%) and the number of uses 217 (17%), antihistamines with a frequency of 25 (10. 55%) %) and the number of uses 197 (15. 44%), vitamins with a frequency of 21 (8. 85%) %) and the number of uses 118 (9. 25%), and finally corticosteroids with a frequency of 14 (5. 91%) %) and the number of uses 87 (6. 82%. Sss+ Meanwhile, based on the type of drug, the highest order with the highest number of drug use were: paracetamol 242 (18. 97%), mucos® 228 (17. 87%) and CTM tablet 197 (15. 43%) and the highest order frequency of prescription was OBH® 100 ml 56 (23. 62%). The highest number of use of the drug in the treatment of upper respiratory tract infections is Paracetamol and the drug with the most frequency is OBH 100 ml.